Indigenous Knowledge of Banyuwangi in Television Program “Bocah Petualang TRANS7” - Rizki Nurislaminingsih; Zulisih Maryani; Saleha Rodiah (Journal of Urban Society's Arts, 2025)
Banyuwangi is famous for its culture as proven by national and international awards. One of the components of culture is indigenous knowledge. The cultural elements of Banyuwangi have also been covered by television stations. TRANS7 created a program that raised the theme of Banyuwangi culture, for example Bocah Petualang. The program, which is known as Si Bolang, not only covered culture, but also practiced indigenous knowledge of Banyuwangi. This study aims to identify local knowledge of Banyuwangi represented by the Bocah Petualang television program. The results of the study show that the Banyuwangi community has local knowledge about traditional games (cars and river rafts), sources of animal protein (bibis, wader, and eel), cooking spices (kecombrang flower), healthy drinks (jamu cabe Jawa and wedang jahe susu), healthy food (watercress decoction and stir-fried durian flowers), livestock (freshwater fish and honey bees), plantations (ranti tomatoes and dragon fruit), handicrafts (bamboo weaving), and dance. The conclusion of this study is that the indigenous knowledge of Banyuwangi in the television program Bocah Petualang is about traditional games, high protein aquatic animals, the benefits of kecombrang, healthy beverages, healthy foods, animal husbandry, plantations, woven ethnomathematics, and motor stimuli in dance art. This study found that insects (spiders) can be used to eradicate pests. The results of this study can be a source of reference for studies about the nutrition of durian flowers. The results of this study can also be a source of inspiration for creative industry practitioners to innovate in creating contents based on local knowledge.